THE ELEMENTS OF GRAMMAR ACTIVITIES IN RAISING LEARNERS’ LANGUAGE AWARENESS - Bakhieva, P. (SCIENCE and SOCIETY, 2025)
The article deals with the attempt to identify the role of activities in teaching languages in developing language awareness, the efficiencies of these exercises in teaching the language. The main focus is given on the elements of grammar activities which are significant in raising learners’ language awareness.